2015
DOI: 10.1111/anu.12211
|View full text |Cite
|
Sign up to set email alerts
|

Expression and characterization of digestive enzyme genes from hepatopancreatic transcripts from redclaw crayfish (Cherax quadricarinatus)

Abstract: Redclaw crayfish, Cherax quadricarinatus, possess a number of biological and commercial attributes that make them ideal for commercial aquaculture. While some studies have investigated digestive enzyme activity and nutritional requirements of this species, little information exists about the expression of digestive enzyme genes and their role in regulating digestive capacity. The current study therefore sequenced and annotated a RNASeq library constructed from a redclaw hepatopancreas to identify genes involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 62 publications
0
5
0
1
Order By: Relevance
“…Yet, a search in the NCBI database revealed that this was the first time that an endo-betamannanase has been reported for the genus Macrobrachium. The enzyme amino acids sequences presented in M. amazonicum have high similarities with two registered species of endogenous mannanase production: Limnoria quadripunctata isopode 81% (King et al, 2010) and Cherax quadricarinatus decapode, 79% (Dammannagoda et al, 2015), and were classified as GH5 family constituent. The enzyme found in the present study was classified as key component for the degradation of structural polysaccharides (mannane) found in plant hemicellulose (Handford et al, 2003).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Yet, a search in the NCBI database revealed that this was the first time that an endo-betamannanase has been reported for the genus Macrobrachium. The enzyme amino acids sequences presented in M. amazonicum have high similarities with two registered species of endogenous mannanase production: Limnoria quadripunctata isopode 81% (King et al, 2010) and Cherax quadricarinatus decapode, 79% (Dammannagoda et al, 2015), and were classified as GH5 family constituent. The enzyme found in the present study was classified as key component for the degradation of structural polysaccharides (mannane) found in plant hemicellulose (Handford et al, 2003).…”
Section: Resultsmentioning
confidence: 87%
“…The utilization of Next Generation sequencing -NGS system enabled the massive sequencing of genes (functional genome), further improving the knowledge in this area. Nine putative functional sequences have been described in C. quadricarinatus (Dammannagoda, Pavasovic, Prentis, Hurwood, & Mather, 2015). This approach has also been used to characterize cellulose-digesting enzymes in M. rosenbergii (Ong et al, 2016) and to provide the transcriptome of M. nipponense under environmental hypoxia (Sun et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Aunque para P. argus se ha demostrado in vitro que la digestión de carbohidratos que provienen de la materia vegetal, como alginato, agar y celulosa, poseen baja hidrólisis (Casuso et al 2014), en algunas langostas de agua dulce, como Cherax quadricarinatus (Xue et al 1999, Dammannagoda et al 2015, Cherax destructor y Euastacus sp. (Linton et al 2006), se han reportado genes que codifican la expresión de enzimas capaces de digerir la celulosa.…”
Section: Resultsunclassified
“…A similar GH5_10 endo-β-1,4-mannase was also expressed in the crayfish Cherax quadricarinatus (Dammannagoda et al 2015;Tan et al 2016). In this species, and in contrast to G. natalis, four transcripts are expressed with their level of expression being lower than that of endo-β-1,4-glucanase (Dammannagoda et al 2015;Tan et al 2016). The putative amino acid sequence of the GH5_10 transcript from G. natalis contained a hydrophobic signal peptide which suggests that it is an extracellular enzyme (Gan et al 2018).…”
Section: Introductionmentioning
confidence: 91%
“…The enzyme was present as a single transcript and had the highest level of expression out of all of the carbohydrases; this included a GH13_24 amylase, a GH9 endo-β-1,4-glucanase and a GH16 β-1,3-glucanase (Gan et al 2018). A similar GH5_10 endo-β-1,4-mannase was also expressed in the crayfish Cherax quadricarinatus (Dammannagoda et al 2015;Tan et al 2016). In this species, and in contrast to G. natalis, four transcripts are expressed with their level of expression being lower than that of endo-β-1,4-glucanase (Dammannagoda et al 2015;Tan et al 2016).…”
Section: Introductionmentioning
confidence: 96%